Clinical relationship between anemia and atrial fibrillation recurrence after catheter ablation without genetic background. (April 2020) - Kim, Min; Hong, Myunghee; Kim, Jong-Youn; Kim, In-Soo; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung; Pak, Hui-Nam
Abstract: Background: Anemia is a known adverse prognostic factor among patients with cardiovascular diseases. We investigated whether the hemoglobin level was associated with the rhythm outcome after atrial fibrillation (AF) catheter ablation (AFCA). Methods: We included 2627 patients who underwent AFCA and a guidelines-based rhythm follow-up (age 58 ± 10.9 years, 73% men, 30.6% with persistent AF), and evaluated the association of pre-AFCA anemia (haemoglobin <13 g/dL in men and <12 g/dL in women) and rhythm outcomes. We studied the mechanistic relationship between anemia and AF recurrence using a Mendelian randomization analysis (1775 subjects with genome-wide association study) after reviewing already proven 12 hemoglobin-associated genetic polymorphisms. Results: The body mass index, paroxysmal AF, warfarin use, and baseline red cell distribution width were independently associated with anemia in patients with AF. During a 23-month follow-up (interval OR 9–48 months), the clinical AF recurrence rate was significantly higher in patients with than without anemia (log-rank p = 0.001; propensity score-matched log-rank p = 0.004). This pattern was more significant in male patients (Log-rank p < 0.001) or patients with paroxysmal AF (Log-rank p < 0.001). Anemia (hazard ratio [HR] 1.45 [1.17–1.80], p = 0.001), left atrial diameter (HR 1.03 [1.01–1.04], p < 0.001), a female sex (HR 1.17 [1.00–1.36], p = 0.047), and persistent AF (HR 1.58 [1.36–1.84], p < 0.001) were independently associated with post-AFCA clinical recurrence. In the Mendelian randomization, we could not find a significant direct causal relationship between anemia and AF recurrence at the genetic level. Conclusions: Pre-AFCA anemia is an independent predictor of post-AFCA clinical recurrence, especially in male patients, without a genetically direct causal relationship.